2021
DOI: 10.3390/infrastructures6050064
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Validation of Steel Slag-Aggregate Concrete for Rigid Pavements: A Full-Scale Study

Abstract: The high wear resistance and toughness of electric arc furnace slag (EAFS) means that this industrial by-product can successfully replace natural aggregate in hydraulic or bituminous concretes that withstand vehicle traffic. This article validates the use of concrete made with large amounts of EAFS for rigid pavements. Accordingly, three EAFS–concrete mixes made with metallic or synthetic fibers were designed. Their performance was studied through laboratory tests (compressive strength, modulus of elasticity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In the last decades, the steel industry in Europe has transitioned towards the electric arc furnace steelmaking technology, being used for approximately 30% of European steel production [15]. In Portugal, there are two steelworks, one located in Seixal (SN Seixal), and the other in Maia (SN Maia), which belong to Siderurgia Nacional (SN) Empresa de Produtos Longos, SA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, the steel industry in Europe has transitioned towards the electric arc furnace steelmaking technology, being used for approximately 30% of European steel production [15]. In Portugal, there are two steelworks, one located in Seixal (SN Seixal), and the other in Maia (SN Maia), which belong to Siderurgia Nacional (SN) Empresa de Produtos Longos, SA.…”
Section: Introductionmentioning
confidence: 99%
“…It is a granular material with a high micro-porosity, very high density, around 3.5 Mg/m 3 , an angular shape, and excellent wear resistance. This slag has excellent properties for use in asphalt mixes, being especially suitable for surface courses where skid resistance and durability are critical functional requirements and for producing asphalt mixes subjected to heavy traffic [15,18,19]. Some previous research has shown that using this material improves the mechanical properties of the asphalt mixtures, such as durability, workability, stiffness, permeability, stability, resistance to fatigue, and permanent deformation [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%